Rb-Sr and Sm-Nd isotopic geochronology of the granitoid and hornblende biotite gneiss from the Oku-iwa Rock in the Lutzow-Holm Complex, East Antarctica - Nishi, Naoko; Kawano, Yoshinobu; Kagami, Hiroo (National Institute of Polar Research, 2002)
P(論文) Oku-iwa Rock in the Liitzow-Holm Complex East Antaictica is situated in a transitional between granulite-facies and amphibolite-facies metamoiphic zones Two gianite masses, the Akai-misaki mass and the Nishi-kaigan mass are intruded into hornblende biotite gneiss (HB gneiss) in this area Rb-Sr and Sm-Nd whole rock isochron ages of the HB gneiss are 583±56 Ma and 674±22 Ma, iespectively The Rb-Sr whole rock isochion age of the Akai-rmsaki gianite mass is 485±50 Ma Some granitoids collected from the Nishi-kaigan gianite mass are plotted close to the 485 Ma ieference isochron with lowei initial^<87>Sr/^<86>Si ratios then the Akai-misaki gianite mass The HB gneiss was foimed from igneous rocks with gianodiontic chemical compositions and/or volcanogeneous sedimentary rocks with similai chemical compositions The HB is characterized by stromatolitic migmatitic appearances Based on present and previously published geochronological data, the following geochronological sequence for Oku-iwa Rock is estimated Stage I (674±22 Ma) was gianodioritic magmatism Stage 2 (583±56 Ma) has two possible interpretations (1) the tempeiature of gianodioiitic rocks formed at ca 670 Ma was giadually lowered and reached ca 700°C at 583 Ma, (2) refusion of granodioiitic rocks which has formed at 674 Ma took place at 583 Ma If the migmatitic portions (leucosome) in the HB gneiss was formed at 674 Ma Oku-iwa Rock must have ictained high temperature between ca 670 Ma and ca 500 Ma (U-Pb ziicon ages ca 620 Ma, 560 Ma-520 Ma) Stage 3 (485±50 Ma) was granitic magmatism Attei 480 Ma the constitutent rocks of Oku-iwa Rock cooled down piobably caused by uplifting departmental bulletin paper